A phase Ib/II study of regorafenib and paclitaxel in patients with beyond first-line advanced esophagogastric carcinoma (REPEAT). (June 2022) - Stroes, Charlotte I; Schokker, Sandor; Khurshed, Mohammed; van der Woude, Stephanie O; Mathôt, Ron AA; Slingerland, Marije; de Vos-Geelen, Judith; Zucchetti, Massimo; Matteo, Cristina; van Dijk, Erik; Ylstra, Bauke; Thijssen, Victor; et al.
Purpose: Regorafenib monotherapy, a multikinase inhibitor of angiogenesis, tumor microenvironment, and tumorigenesis, showed promising results in gastric cancer. We aimed to assess the tolerability of regorafenib and paclitaxel in patients with advanced esophagogastric cancer (EGC) refractory to first-line treatment, and explore potential biomarkers. Methods: Patients received paclitaxel (80 mg/m 2 ) on days 1, 8, and 15 of a 28-day cycle and regorafenib (80/120/160 mg) on days 1–21 in the dose-escalation cohort, and the maximum-tolerated dose (MTD) in the dose-expansion cohort. Exploratory, overall survival (OS) and progression-free survival (PFS) were compared to a propensity-score matched cohort receiving standard second-/third-line systemic treatment. Paclitaxel pharmacokinetics were assessed using samples from day 1 (D1) and day 15 (D15). We performed enzyme-linked immunosorbent assay measurements of galectin-1, RNA sequencing, and shallow whole-genome sequencing of metastatic tumor biopsies for biomarker analyses. Results: In the dose-escalation cohort ( n = 14), the MTD of regorafenib was 120 mg. In all, 34 patients were enrolled in the dose-expansion cohort. Most common toxicities (all grades; grade ⩾ 3) were fatigue (79%; 4%) and sensory neuropathy (63%; 4%). Best responses achieved were partial response (28%) and stable disease (54%). Median OS and PFS were 7.8 and 4.2 months, respectively (median follow-up: 7.8 months). OS ( p = 0.08) and PFS ( p = 0.81) were not significantly improved compared to the matched cohort. Paclitaxel concentrations were significantly increased with regorafenib (D15) compared with paclitaxel only (D1; p < 0.05); no associations were observed with toxicity or efficacy. An increase in circulating galectin-1 compared to baseline was associated with shorter OS ( p < 0.01). Enrichment of angiogenesis-related gene expression was observed in short survivors measured by RNA sequencing. Chromosome 19q13.12-q13.2 amplification was associated with shorter OS ( p = 0.02) and PFS ( p = 0.02). Conclusion: Treatment with regorafenib and paclitaxel is tolerable and shows promising efficacy in advanced EGC refractory to first-line treatment. Galectin-1 and chromosome 19q13.12-q13.2 amplification could serve as negative predictive biomarkers for treatment response. Registration: Clinicaltrials.gov, NCT02406170, https://clinicaltrials.gov/ct2/show/NCT02406170